Jam’iyah Keagamaan Sebagai Agen Harmoni Sosial Dan Pencegahan Konflik Masyarakat Di Desa Selotambak: Peran Jam’iyah Keagamaan dalam Membangun Harmoni Sosial dan Pencegahan Konflik Masyarakat Pedesaan - Jami’ Shobri; Laili Mas Ulliyah Hasan (Sekolah Tinggi Agama Islam Al-Muntahy, 2025)
This study focuses on empowering religious associations (jam’iyah keagamaan) as agents of social harmony and conflict prevention in rural communities, with a case study conducted in Selotambak Village. The main objective is to identify and analyze the role of jam’iyah in strengthening social cohesion, fostering collective awareness of tolerance, and developing a community empowerment model based on religious values. A qualitative approach with a participatory case study design was employed, using data collected through field observation, in-depth interviews, and document analysis. The data were analyzed interactively through reduction, presentation, and conclusion drawing, interpreted within the frameworks of social capital theory and community-based peacebuilding. The findings reveal that jam’iyah plays a significant role in reinforcing social solidarity, facilitating peaceful communication among residents, and reducing the intensity of social conflicts within the community. Increased participation in jam’iyah activities correlates positively with the growth of social trust and awareness of the importance of peaceful coexistence. The implications of this activity extend beyond community engagement by offering a spiritually grounded empowerment model relevant to sustainable social development. Overall, the study demonstrates that local religious institutions can function as effective peacebuilding agents and social stabilizers within plural rural societies.